Expectations and the 1994 Maine Elections - Potholm, Christian (Maine Policy Review, 1994)
The 1994 elections at the national and state level resulted in significant changes all across the political landscape. Bowdoin professor of government Christian Potholm analyzes the nature of that change and its implications forMaine.
Keywords: Maine elections